Diverse forests are cool: Promoting diverse forests to mitigate carbon emissions and climate change. Issue 1 (15th November 2021) - Beugnon, Rémy; Ladouceur, Emma; Sünnemann, Marie; Cesarz, Simone; Eisenhauer, Nico
Abstract: Climate change is one of the most pressing threats to humanity, inducing a global increase in temperatures and more frequent extreme climatic events. Considering this, global reforestation initiatives are proposed to capture carbon and mitigate climate change. Global restoration and reforestation programs and their targets have inspired both unparalleled enthusiasm worldwide and intense scientific criticism and debate regarding their feasibility and implementation. We agree that global reforestation forecasting and efforts require a nuanced discussion and approach. In that vein, we would like to emphasize the potential of increasing existing forest diversity to enhance climate change mitigation by increasing aboveground and belowground carbon storage. Moreover, we argue that focusing on planting diverse forests in reforestation efforts can help to reduce climate change effects on ecosystems: first, by increasing resistance and resilience to extreme climatic events, and second, by buffering microclimatic conditions in natural and urban areas. Diversifying forests plantations and reforestation projects may not always be feasible and cannot solve the climate crisis by itself. However, we highlight that a focus on diverse forests could maximize the benefits of reforestation programs by promoting sustainable land management. Abstract : Climate change is one of the most pressing threats to humanity, inducing a global increase in temperatures and more frequent extreme climatic events. We would like to emphasize the potential of increasing forest diversity to enhance climate change mitigation by increasing aboveground and belowground carbon storage. Moreover, we argue that focusing on planting diverse forests in reforestation efforts can help to reduce climate change effects on ecosystems: first, by increasing resistance and resilience to extreme climatic events, and second, by buffering microclimatic conditions in natural and urban areas.